Circumferential cutaneous papilloma on the external auditory canal presenting as chronic otitis externa - Subtil, João (2014)
Introduction: The authors present a case of a circumferential cutaneous papilloma on the external auditory canal wrongly diagnosed and unsuccessfully treated as chronic otitis externa during fifteen years. This case is interesting for the unusual location and extension of this papilloma, as well as for the treatment used for eradicating the disease with no complication. Material and methods: The external ear canal and tympanic membrane on both ears showed circumferential lesions suggesting cutaneous papilloma, confirmed by histology of biopsy specimen. Surgical treatment was withheld because of unacceptable morbidity and instead was treated with topical imiquimod. Results: Complete resolution was obtained after twelve weeks of treatment, and no recurrence was observed after one year. Conclusions: Imiquimod has been used as a topical agent with an important action over the cutaneous immune system, and is being growingly accepted as an alternative treatment for aggressive or difficult skin problems, such as the one we present.